The persistence of racialization - Kirschner, Luz Angélica, author. Link
1 online resource.
Keywords: "The Persistence of Racialization: Literature, Gender, and Ethnicity represents the attempt at unpacking the legacy of modern ideas of race initiated and established during the conquest of the Americas and their current relevance for literary criticism of ethnic writing, also known as minority writing. The book challenges ideas of a post-racial globalized world to question the tendency to devaluate ethnic literary writing in general, and ethnic women's productions in particular, by questioning reductive literary criticism of ethnic writing that perpetuates bias against ethnic writing and its authors. By advocating for a decolonial literary imagination, the book urges literary critics of ethnic writing to consider the complexities of modern race and its enduring impact on contemporary social and cultural narratives. Updated literary analyses of Jewish Argentine, Turkish German, and Chinese American women writers encourage literary critics of ethnic writing to explore alternative transnational frameworks that prioritize equity, diversity, and social justice"--